Surgical and Health-related Quality-of-Life Outcomes of Growing Rod "Graduates" With Severe versus Moderate Early-onset Scoliosis. Issue 10 (15th May 2019) - Helenius, Ilkka J.; Sponseller, Paul D.; McClung, Anna; Pawelek, Jeff B.; Yazici, Muharrem; Emans, John B.; Thompson, George H.; Johnston, Charles E.; Shah, Suken A.; Akbarnia, Behrooz A.
Abstract : Study Design: A retrospective review of a prospective, multicenter database. Objective: The aim of this study was to compare surgical and quality-of-life outcomes at the end of growing rod treatment in patients with severe versus moderate early-onset scoliosis (EOS). Summary of Background Data: Knowledge of the outcomes of severe EOS after growth-friendly treatment is limited because this condition is uncommon. Methods: We identified 40 children with severe EOS (major curve ≥90°) treated with growing rods before age 10 with minimum 2-year follow-up after last lengthening or final fusion. From the same registry, we matched 40 patients with moderate EOS (major curve < 90°). Twenty-seven patients in the severe group and 12 in the moderate group underwent final fusion ( P  < 0.001). Results: Mean preoperative curves were 102° (range, 90°–139°) in the severe group and 63° (range, 33°–88°) in the moderate group ( P  < 0.001). At final follow-up, mean curves were 56° (range, 10°–91°) and 36° (range, 12°–89°), respectively ( P  < 0.001). Fourteen (35%) children in the severe group and 32 (80%) in the moderate group had scoliosis of < 45° at final follow-up [risk ratio (RR), 0.44; 95% confidence interval (95% CI), 0.20–0.57]. At final follow-up, 30 (75%) children in the severe group and 35 (88%) in the moderate group had achieved T1-T12 length of ≥18 cm (RR, 0.86; 95% CI, 0.70–1.09). Thirty-five children in the severe group and 26 in the moderate group had at least one complication (RR, 1.35; 95% CI, 1.05–1.73). Mean 24-Item Early-Onset Scoliosis Questionnaire scores were similar between groups at final follow-up. Conclusion: Delaying surgery until the major curve has progressed beyond 90° is associated with larger residual deformity and more complications than treating at a lesser curve magnitude. Quality-of-life outcomes were similar between those with severe and moderate EOS. Level of Evidence: 3 Abstract : Growing rod treatment achieved T1-T12 length of ≥18 cm in most children with severe EOS. One-third of patients with severe EOS had scoliosis of <45° at the end of growth-friendly treatment. The highest score of the 11 domains in the EOSQ-24 questionnaire was for pulmonary function in both groups.